Professional Development Program on Innovative Teaching Strategies for Novice Science Teachers - Diana Ayu Rostikawati; Ari Widodo; Riandi; Diana Rochintaniawati; Wahyu Sopandi (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
This study aimed to provide professional development to beginner teachers for modifying science teaching strategies innovatively.The program involved 15 primary teachers with diverse genders, ages, educational backgrounds, and teaching experience. The program was developed through a four-stage training model: reflection, identification, analysis, and modification. The study assessed participants' understanding of innovative science teaching through a pre-test, post-test, journals, worksheets, and lesson plans with data analyzed descriptively and qualitatively. Results showed that most teachers (73.3%) could participate in the training stages optimally, which increased their competence in modifying innovative science teaching strategies. However, some teachers needed help during the training process, which was influenced by factors such as educational background and teaching experience. The study found that a teacher’s educational background and teaching experience positively influence their competence, with better alignment and more experience enhancing pedagogical skills. A training program fostered lifelong learning, motivating teachers to create development plans. Teachers also formed learning communities through social media, enhancing collaboration and professional growth.